Solve for q -2=-10q-(-8q+1)

Math
-2=-10q-(-8q+1)
Rewrite the equation as -10q-(-8q+1)=-2.
-10q-(-8q+1)=-2
Simplify -10q-(-8q+1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-10q-(-8q)-1⋅1=-2
Multiply -8 by -1.
-10q+8q-1⋅1=-2
Multiply -1 by 1.
-10q+8q-1=-2
-10q+8q-1=-2
Add -10q and 8q.
-2q-1=-2
-2q-1=-2
Move all terms not containing q to the right side of the equation.
Tap for more steps…
Add 1 to both sides of the equation.
-2q=-2+1
Add -2 and 1.
-2q=-1
-2q=-1
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2q=-1 by -2.
-2q-2=-1-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2q-2=-1-2
Divide q by 1.
q=-1-2
q=-1-2
Dividing two negative values results in a positive value.
q=12
q=12
The result can be shown in multiple forms.
Exact Form:
q=12
Decimal Form:
q=0.5
Solve for q -2=-10q-(-8q+1)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top